Development of automatic driving system on rough road-automatic steering control by fuzzy algorithm - Shigematu, T.; Hashimoto, Y.; Watanabe, T. (IEEE Intelligent Vehicles, 1992, 1992)
The automatic control method for the vehicle driving test on rough road is discussed. The main requirement of the automated test is that the stress on the vehicle is equivalent to the one given by a driver's test. In the first step, the evaluated indices of control performance are chosen as the tracking ability for the target course and the approximation of steering pattern for the driver operation. Next, a driver steering model is modified into a control algorithm which can be applied to rough road driving. The essential conditions of the improved algorithm are: (1) stability analysis, and ( 2) optimized parameters. The subjects are solved by the stability criterion of a linear system for (1) and by introducing fuzzy logic for ()2). Finally, the system composition for realizing the control system has been studied, and evaluation tests have been conducted by driving the vehicle on a rough road course.< >